President’s Message - Socha, Linda (Operating Room Nurses Association of Canada Journal, 2007)
Patient safety has long been considered a priority in Canada – provincially and nationally. Within the last few years, however, the profile of patient safety initiatives has skyrocketed. Numerous initiatives and organizations have been launched in an effort to improve the safety of Canadian patients throughout the healthcare spectrum. Current provincial initiatives include Health Quality Councils established in some provinces to report on quality, safety and performance of health services and health systems. Other provinces have created patient safety task forces to promote and facilitate activities that have a positive impact on patient safety. Developing a culture of open communication to report adverse events or “near misses” has also been on every province’s agenda in healthcare. Open exchanges about adverse events and systems leads to a better understanding of where and why errors occur.